Functional polymer‐dependent 3D culture accelerates the differentiation of HepaRG cells into mature hepatocytes. Issue 10 (7th February 2016) - Higuchi, Yichiro; Kawai, Kenji; Kanaki, Tatsuro; Yamazaki, Hiroshi; Chesné, Christophe; Guguen‐Guillouzo, Christiane; Suemizu, Hiroshi
Abstract : Aim: The hepatoma‐derived cell line HepaRG is regarded as an in vitro model of drug metabolism because fully differentiated HepaRG cells demonstrate functional metabolic responses comparable to those of primary human hepatocytes. Recently, it was demonstrated that the 3D culture of HepaRG cells enhanced their metabolic functions and toxicological responses. We approached the mechanisms underlying these enhancement effects. Methods: We compared 2D‐cultured HepaRG cells with 3D‐cultured HepaRG spheroids in the gene expression patterns and the metabolic functions. In the present study, we performed 3D culture of HepaRG cells using functional polymers (FP). To reveal the in vivo differentiation ability, we transplanted the 3D‐cultured HepaRG spheroids into TK‐NOG mice. Results: A comparison between 2D and 3D cultures revealed that 3D‐cultured HepaRG spheroids demonstrated reductions in bile duct marker expression, accelerated expression of cytochrome P450 3A4, and increases in the ratio of albumin‐expressing hepatocytes. Furthermore, catalytic activities of cytochrome P450 3A4 were modified by omeprazole and rifampicin in the 3D‐cultured HepaRG spheroids. Transplantation analysis revealed that 3D‐cultured HepaRG spheroids formed hepatocyte‐like colonies rather than cholangiocytes in vivo . Conclusion: Our results indicated that the enhancement of hepatic functions in 3D‐cultured HepaRG cells was induced by selective hepatocyte differentiation and accelerated hepatocyte maturation. HepaRG spheroids reproduced the metabolic responses of human hepatocytes. Therefore, FP‐dependent 3D‐cultured HepaRG cells may serve as an excellent in vitro model for evaluating the hepatic metabolism and toxicity.